Presentation of obstructive left heart malformations in infancy. Issue 3 (November 1994) - Abu-Harb, M; Wyllie, J; Hey, E; Richmond, S; Wren, C
Abstract : This study documents the presentation of acutely life threatening congenital heart disease in infancy in order to assess the performance of screening examinations soon after birth and at 6 weeks of age. All cases of obstructive left heart malformations presenting in infancy in one health region from 1987-91 were analysed retrospectively. Altogether, 120 infants presented with either hypoplastic left heart syndrome, interruption of the aortic arch, coarctation of the aorta, or aortic valve stenosis. Twelve became symptomatic or died within 24 hours. Thirty four had an abnormal neonatal examination, eight of whom were referred. Six more became symptomatic before discharge. Ninety four babies went home, 51 developed heart failure before 6 weeks, and another seven died without diagnosis. Twenty five of 36 (69%) reaching 6 weeks without diagnosis had a second examination which was abnormal in 17. Two babies died undiagnosed after 6 weeks and the other 18 presented at up to 11 months of age. The neonatal and 6 week examinations perform poorly as screening tests for congenital heart disease. A normal neonatal examination does not exclude life threatening congenital heart disease.